2016
DOI: 10.1007/978-3-319-29938-9_2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the User Experience of Password Reset Policies in a University

Abstract: Organisations often provide helpdesk services to users, to resolve any problems that they may have in managing passwords for their provisioned accounts. Helpdesk logs record password change events and support requests, but overlook the impact of compliance upon end-user productivity. System managers are not incentivised to investigate these impacts, so productivity costs remain with the end-user. We investigate how helpdesk log data can be analysed and augmented to expose the user's personal costs. Here we des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Account remediation is not only a protocol that websites should follow; it is a complex way that brings in the sociotechnical components to ensure data protection and prevent further data leakage for an account compromise. Additionally, the proper account remediation process enables users to protect their accounts as a preventive measure through secure behavior such as prevention of password rotation [65], [77]. Our transcontinental analysis for the 158 websites measures the account remediation for different aspects like changing passwords, reviewing past activities, enabling 2FA, and others.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Account remediation is not only a protocol that websites should follow; it is a complex way that brings in the sociotechnical components to ensure data protection and prevent further data leakage for an account compromise. Additionally, the proper account remediation process enables users to protect their accounts as a preventive measure through secure behavior such as prevention of password rotation [65], [77]. Our transcontinental analysis for the 158 websites measures the account remediation for different aspects like changing passwords, reviewing past activities, enabling 2FA, and others.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…As part of this study, we checked website password requirements and found that, on average, 53% of them do not check for a proper password rotation [65], [77]. This check is possible without any security infringement, as knowledge of the old password also needs to be double-checked.…”
Section: Robust Security Requirementsmentioning
confidence: 99%